Irrational Beliefs, Life Orientation and Temporal Perspective of Prison Inmates - Morris, G. Barry; Zingle, Harvey (Canadian Journal of Counselling and Psychotherapy, 2012)
This study investigated the psychological health of criminals based on Albert Ellis' Rational-Emotive Theory. Other dimensions of mental health examined were the criminals' life orientation, and temporal perspective.The Adult Irrational Ideas Inventory, Life Orientation Test, Wallace Temporal Perspective Technique and a Biographical Data Inventory were administered to 104 male prison inmates and 63 non-institutionalized males from the general population. Findings indicated that the criminal sample possessed significantly more irrational beliefs and were less future oriented than non-criminals. Irrational beliefs, indicating self-centerednessa nd control of others, were most strongly adhered to by the prisoners.Future oriented prisoners were largely determined as being the eldest in their families, incarcerated for longer periods of time, and having unfavorable impressions of the institution. Implications for further research were also presented.